Finding the Sweet Spot: How Human Fungal Pathogens Acquire and Turn the Sugar Inositol against Their Hosts - Xue, Chaoyang (mBio, 2015)
Inositol is an essential nutrient with important structural and signaling functions in eukaryotes. Its role in microbial pathogenesis has been reported in fungi, protozoans, and eubacteria. In a recent article, Porollo et al. [mBio 5(6):e01834-14, 2014, doi:10.1128/mBio.01834-14] demonstrated the importance of inositol metabolism in the development and viability of Pneumocystis species—obligate fungal pathogens that remain unculturable in vitro. To understand their obligate nature, the authors used innovative comparative genomic approaches and discovered that Pneumocystis spp. are inositol auxotrophs due to the lack of inositol biosynthetic enzymes and that inositol insufficiency is a contributing factor preventing fungal growth in vitro. This work is in accord with other studies suggesting that inositol plays a conserved role in microbial pathogenesis. Inositol uptake and metabolism therefore may represent novel antimicrobial drug targets. Using comparative genomics to analyze metabolic pathways offers a powerful tool to gain new insights into nutrient utilization in microbes, especially obligate pathogens.